Erratum: Nemésio, A. & Ferrari, R.R. (2011) Species of Euglossa (Glossura) and E. (Glossuropoda) (Hymenoptera: Apidae: Euglossina) occurring in the Amazon, including new records for Brazil. Zootaxa, 2885, 1–13. - Nemésio, A.; Ferrari, R. R. (Zootaxa, 2011)
(Erratum)